Towards an Access Paradigm in Innovation Law?. Issue 10 (7th April 2021) - Leistner, Matthias
Abstract: The article generally discusses today's meaning of an access paradigm in innovation law. Starting from concrete examples of access problems, it examines future research perspectives and the respective role of an access paradigm in innovation law. This concerns inter alia the possibility of common principles for public interest exceptions, in particular exceptions in the interest of free competition, throughout the different IP rights, as well as a closer look at the possibility of IP-external, sector-specific access regulation and the principles which should guide such approaches in research and policy.